Global scientific trends on thyroid disease in early 21st century: a bibliometric and visualized analysis - Song, Mingyuan; Sun, Wei; Liu, Qi; Wang, Zhongqing; Zhang, Hao (Frontiers in Endocrinology, 2024)
Background Bibliometrics has been used to analyze the literature in the field of thyroid disease studies in the early 21st century, indicating the changes in current international study trends. Methods In this study, a bibliometric analysis of data retrieved from the Web of Science (WoS) database was conducted, and the publication trends and thematic evolution in the field of thyroid disease research from January 1, 2000, to November 16, 2022, were analyzed. A total of 69283 articles related to thyroid diseases were evaluated for their characteristics, including annual publication volume, countries, journals, institutions, authors, keywords, and references. VOSviewer was utilized to perform the analysis of co-authorship, co-citation, co-occurrence and descriptive. Results The annual publication volume of thyroid disease research literature showed a fluctuating upward trend from 2000 to 2021, exceeding 5,000 articles for the first time in 2021. The United States (16120 counts, 678255 cities) ranks first in terms of publication volume and citation. Thyroid (n=3201) and Journal of Clinical Endocrinology&Metabolism (n=140399) are the most prolific and cited journals, respectively. The organization with the highest publication volume and citation frequency is Harvard University (1011 counts, 59429 cities), Miyauchi Akira (n=422), Schlumberger, and Martin (n=24839) possess the highest publication volume and citation frequency, respectively. Co-occurrence analysis of 307 keywords with frequencies of more than 20 resulted in 6 clusters (1): Thyroid dysfunction and diseases (2); mechanism of occurrence and development of thyroid cancer (3); autoimmune thyroiditis (4); scope and postoperative management of thyroid surgery (5); fine needle aspiration of thyroid nodules (6); radioactive iodine therapy for thyroid cancer. Active monitoring, thermal ablation, Lenvatinib, and long noncoding RNA refer to the latest keywords. Discussing the six clusters helps scholars to determine the scope and direction of studies. Conclusion Over the past two decades, the literature related to thyroid diseases has increased year by year, with closer collaboration between countries, institutions, and authors. In this study, the global trends, research hotspots, emerging subjects, and basic knowledge of literature related to thyroid diseases were respectively elucidated, which will facilitate researchers in this field to seek better development.